A basic guide to international business law - Wevers, H. (Noordhoff Uitgevers Groningen, 2021)
"A Basic Guide to International Business Law aims to give students an understanding as well as practical knowledge of legal problems arising in the area of international business, and to equip them with the skills needed to prevent and tackle these problems. All Chapters employ the same didactic structure. Introductory case studies, examples, annotated case law, glossaries, diagrams, summaries and exercises are all designed to familiarize students quickly with relevant aspects of international (business) law..."--Back cover.